COST PLANNING BANGUNAN GEDUNG SEDERHANA DENGAN COST SIGNIFICANT MODEL DI KABUPATEN HULU SUNGAI SELATAN (Studi Kasus Proyek PKM di Hulu Sungai Selatan) - Candra Yuliana; Aulia Isramaulana; M. Dzulfi Khairiannoor (Jurnal Infrastruktur, 2021)
Project cost estimates must be prepared before the project is implemented. The Cost Significant Model is a model of estimating total construction costs, based on past construction data using the Pareto Principle. The purpose of this research is to apply the method of cost significant models to a building project to determine the initial cost of a building project. The estimated cost per m2 model is Y = 11,564 (X3) + 2949750.72, where X3 is the cost per m2 of foundation, sloof, and floor work. The accuracy of the Cost Significant Model ranges from -9.4% to 4.8%. This estimation model is feasible to be used to check the estimated offer.